Mine Development And Underground Construction Of Andes Copper Mining Co. At Potrerillos, Chile - I. L. Greninger (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
THE property of the Andes Copper Mining Co. is in the central part of the Republic of Chile, Province of Atacama, 147 km. (91.5 miles) eastward by rail from the port of Chañaral. At this point the Andean system is made up of two principal ranges. The mine is on the westerly slope of the outer, or western, range, at a mean elevation of 3250 m. (10,500 ft.). A meter-gage railroad extends from the company's port at Barquito, near Chañaral, to the reduction plant at Potrerillos. This road has a total length of 151 km. (94.0 miles), of which 93 km. (57.79 miles) are owned by the Andes Copper Mining Co. The remainder of the road is owned by the state. The company operates its trains over the portion of the road owned by the state, under an agreement with the Chilean Government. The mine is connected with the reduction plant by a meter-gage railroad, 10 km. (6.214 miles) long, which extends from the coarse ore bins at the metallurgical plant to the underground storage bins at the mine. Tunnels make up 60 per cent. of the total length of this railroad. As is characteristic of the Andean region in Chile, the topography of the locality is extremely rough, and a number of points near the mine have elevations of from 15,000 to 16,000 feet.